Your job is easy - Sommer, Carl, 1930-; James, Kennon (Houston, TX : Advance Pub., 2000)
When a mother and father exchange jobs for a day, they each come to respect the value of what the other does.
Keywords: Farm life -- Fiction; Families -- Fiction; Work -- Fiction